Thickness debit effect in Ni-based single crystal superalloys at different stress levels. (15th March 2020) - Yu, Z.Y.; Wang, X.M.; Liang, H.; Li, Z.X.; Li, L.; Yue, Z.F.
Highlights: Growth law of γ' depleted regions followed the power function at high temperature. γ' depleted regions near the surface produced voids growth in the interior bulk area. Great stress intensity factor in thin specimens led to a reduced creep rupture life. The thickness debit effect was only significant at low stress levels. Abstract: In order to investigate the mechanism of thickness debit effect at different stress levels, creep tests of thin-walled Ni-based superalloys were conducted under three test conditions: 220 MPa, 275 MPa and 330 MPa at 980 °C. Results showed that the creep life reduced with the decrease of specimen thickness at 220 MPa and 275 MPa. At 330 MPa, this variation tendency was not so evident. Metallographic observations revealed that the specimen thickness and the external stress level affected the depth of γ' depleted region and the distribution of voids and cracks of the specimen. Thus, a phase-field model and a crack growth model were used to consider the influence of γ' depleted region and crack growth on life, respectively. It was found from the phase-field model that the existence of γ' depleted region led to more considerable plastic strain and equivalent stress in the normal γ/γ' phase region than that in the γ' depleted region. This phenomenon was more evident in the thin specimen at low stress level. At high stress level, the redistribution of the stress field was not so distinct due to the premature plastic deformation in the normal γ/γ' phase region. The crack growth models showed a shorter critical value of the crack length and faster crack propagation in the thin specimen. However, the increased external stress levels would decrease the disparity of cracks propagation between the thin and thick samples. Comprehensive consideration of the phase-field method and the crack growth model revealed the thickness debit effect at different stress levels. Graphical Abstract: "Complex Type" phase-field model combined with the crack growth model analyzed the mechanical behavior of the thin-walled superalloys at different stress levels Image, graphical abstract .